Characteristics of masticatory muscles in children with unilateral posterior crossbite - Annicele da Silva Andrade; Maria Beatriz Duarte Gavião; Gustavo Hauber Gameiro; Moara De Rossi (Sociedade Brasileira de Pesquisa Odontológica, 2010)
The aim of this study was to detect possible differences in the EMG (electromiography) activity, chewing rate (CR), cycle duration (CD) and preferred chewing side (PCS) between children with and without unilateral posterior crossbite. Thirty-seven children aged from 7 to 10 years were selected from the clinic of the Department of Pediatric Dentistry, Piracicaba Dental School, Brazil, and divided into two groups: unilateral posterior crossbite (UPCB group, n = 17), and normal occlusion (NOccl group, n = 20). The PCS was determined using a visual spot-checking method. The EMG activity was recorded during mastication, and two chewing sequences of 20 s were evaluated to establish each subject's CR (cycles/sec) and CD. UPCB and NOccl groups did not have a PCS. The EMG activity and the cycle characteristics did not differ between the groups. The correlations between CD, CR and EMG activity were statistically significant for the masseter and anterior temporalis muscles only in the NOccl group, in which there was also a significant correlation between the EMG activity of masseter and anterior temporalis. In conclusion, these findings suggest that although children with and without UPCB presented a bilateral masticatory pattern with similar CR and CD, balanced EMG activity of masseter and anterior temporalis muscles was observed only in the NOccl group. These results indicate that in children, UPCB can alter the coordination of masticatory muscles during mastication.